Utilization of breast cancer screening with magnetic resonance imaging in community practice - Hill, Deirdre A. (J Gen Intern Med, 2017)
BACKGROUND: Breast cancer screening with magnetic resonance imaging (MRI) may be a useful adjunct to screening mammography in high-risk women, but MRI uptake may be increasing rapidly among low- and average-risk women for whom benefits are unestablished. Comparatively little is known about use of screening MRI in community practice. OBJECTIVE: To assess relative utilization of MRI among women who do and do not meet professional society guidelines for supplemental screening, and describe utilization according to breast cancer risk indications. DESIGN: Prospective cohort study conducted between 2007 and 2014. PARTICIPANTS: In five regional imaging registries participating in the Breast Cancer Surveillance Consortium (BCSC), 348,955 women received a screening mammogram, of whom 1499 underwent screening MRI. MAIN MEASURES: Lifetime breast cancer risk (< 20% or ≥ 20%) estimated by family history of two or more first-degree relatives, and Gail model risk estimates. Breast Imaging Reporting and Data System breast density and benign breast diseases also were assessed. Relative risks (RR) for undergoing screening MRI were estimated using Poisson regression. KEY RESULTS: Among women with < 20% lifetime risk, which does not meet professional guidelines for supplementary MRI screening, and no first-degree breast cancer family history, screening MRI utilization was elevated among those with extremely dense breasts [RR 2.2; 95% confidence interval (CI) 1.7–2.8] relative to those with scattered fibroglandular densities and among women with atypia (RR 7.4; 95% CI 3.9–14.3.) or lobular carcinoma in situ (RR 33.1; 95% CI 18.0–60.9) relative to women with non-proliferative disease. Approximately 82.9% (95% CI 80.8%–84.7%) of screening MRIs occurred among women who did not meet professional guidelines and 35.5% (95% CI 33.1–37.9%) among women considered at low-to-average breast cancer risk. CONCLUSION: Utilization of screening MRI in community settings is not consistent with current professional guidelines and the goal of delivery of high-value care.